2021
DOI: 10.3390/su13020602
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Calculus in Adopting Smart Speakers—Personalized Services and Privacy Risks

Abstract: Despite the benefits of using smart speakers, serious privacy concerns have been raised, particularly due to their constantly listening microphones. Given the mixture of the advantages and risks deciding whether to use them is not an easy matter, casting a doubt about sustainable growth and development of smart speakers. Using a sample of 559 users in South Korea and the U.S., we empirically investigated the dilemma of users seeking to adopt smart speakers. The results revealed users’ perceived usefulness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Prior studies have verified that individuals with frequent experiences of privacy disclosure are less sensitive about their personal information (Lang et al, 2018). In a similar vein, given that privacy-related issues have become a significant issue owing to the development of ICT and the high frequency of privacy-providing experiences using mobile devices in the pandemic situation (Cha et al, 2021), we also considered that the duration of smartphone usage would affect personal information disclosure intentions.…”
Section: Research Modelmentioning
confidence: 99%
“…Prior studies have verified that individuals with frequent experiences of privacy disclosure are less sensitive about their personal information (Lang et al, 2018). In a similar vein, given that privacy-related issues have become a significant issue owing to the development of ICT and the high frequency of privacy-providing experiences using mobile devices in the pandemic situation (Cha et al, 2021), we also considered that the duration of smartphone usage would affect personal information disclosure intentions.…”
Section: Research Modelmentioning
confidence: 99%
“…This evidence supports H3 . Indeed, as privacy risk increases, the effect of smart speaker ease of use on smart speaker usefulness decreases, which shows that privacy risks affect smart speakers’ usefulness because of consumers’ concerns about their data (Cha et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the fear of losing control over personal information (Connolly and Bannister, 2007) and losing control over the ability to make freewill decisions (Walter and Lopez, 2008). Indeed, previous studies showed that perceived privacy risks affect the intention to use smart speakers because of consumers’ concerns about their data (Cha et al , 2021).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The most recurring (negative) factor for adoption is the presence of privacy concerns. This is explicitly highlighted in Lau et al, 3 Kefi et al, 47 Burbach et al, 50 Furini et al, 53 Hugo et al, 58 Cha et al, 59 Bawack et al 64,65 This is particularly interesting when both users and non-users are considered, as in Burbach et al, 50 since users may be affected by bias (they have somewhat overcome their privacy concerns). On the other hand, users appear willing to trade privacy for convenience.…”
Section: Adoption Factorsmentioning
confidence: 99%
“…4 Usefulness (and ease of use) play a major role in Choi et al 54 (where older adults are considered). Utilitarian and hedonic factors are seen as major factors, 59 in particular increasing the willingness to disclose information. 57 With a few exceptions, most papers do not examine specific usage contexts.…”
Section: Adoption Factorsmentioning
confidence: 99%